THE DEVELOPMENT OF CIPATUJAH BEACH'S POTENTIAL AS A TOURISM DESTINATION IN TASIKMALAYA REGENCY - Hubertina Ngarbingan; Yulita Suryantari (Universitas Terbuka, 2022)
The purpose of this research is to determine the potency that can be developed in Cipatujah Beach as a tourism destination in Tasikmalaya Regency. The potency of Cipatujah Beach is categorized based on Cooper theory (2000), those are 4 A aspects: attraction, accessibility, amenities and ancillary. Based on the results of data analysis, Cipatujah Beach has been qualified to reach those aspects with the right development plan. The research method that is used in this research is descriptive qualitative method. The techniques of collecting the data are in-depth interview, observation, and triangulation. The technique of analyzing the data is SWOT analysis. The result of this research shows that Cipatujah Beach can be developed as a tourism destination by utilizing those aspects optimally. Besides, cooperation of stakeholders, local people and tourism industry is very required to create a good and systematic development, to keep the tourism sustainability. Tourism sustainability is an appropriate approach of Cipatujah Beach development as a considered tourism destination for the next generation without defaces the originality of tourism destination. Keywords: Attraction, Accessibility, Amenity, Ancillary, Sustainability Tourism.